Estandarización de protocolos para la preservación y manejo de la colección biológica de artrópodos del mauq (2017)
The Museum of Arthropods of the University of Quindío hold on one of the largest collections of entomology from coffee region and the north of the Valle of Cauca, for that reason was necessary to elaborate the protocols for the management of the collection. These documents were elaborated for describe the activities to be carried out in relation to the specimens deposited and were aimed at guaranteeing the good quality, conservation and legal administration of these. The guidelines were standardized and the results was in the elaboration of eleven protocols, in which The procedures to be performed when entering, removing, preserving and keeping on copies of both the collection dedicated to research and the specimens used for exhibition and teaching. Similarly, safety protocols were developed within the facilities, internships, volunteers, use of equipment and assets. In addition to this we analyzed the current compliance of the MAUQ with the correct practices and it was observed that the safety guidelines in the facilities are not correct since they are in a low category, contrary to the protocol for internships and volunteers which has a high level; In terms of the procedures that guarantee the durability of the specimens present a middle category which showed us the lack of a curator within the MAUQ collection.